Johann André : Geboh. 28 März 1741. Gest. 18 Jüny 1799 - Lips, Johann Heinrich, 1758-1817 (engraver):::Creator::::::::::::; May, Georg Oswald, 1738-1816 (artist):::Contributor:::::::::::: (Switzerlan; Zürich)
Portrait engraving of Johann André by Johann Heinrich Lips based on the painting by Georg May.